2021
DOI: 10.3390/a14040123
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Tour Length for the Close Enough Traveling Salesman Problem

Abstract: We construct empirically based regression models for estimating the tour length in the Close Enough Traveling Salesman Problem (CETSP). In the CETSP, a customer is considered visited when the salesman visits any point in the customer’s service region. We build our models using as many as 14 independent variables on a set of 780 benchmark instances of the CETSP and compare the estimated tour lengths to the results from a Steiner zone heuristic. We validate our results on a new set of 234 instances that are simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Ref. [40] proposed a branch-andbound algorithm to address the CETSP in two and three dimensions, and [17] presented a method to estimate previously a tour length from the knowledge of several variables. Refs.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Ref. [40] proposed a branch-andbound algorithm to address the CETSP in two and three dimensions, and [17] presented a method to estimate previously a tour length from the knowledge of several variables. Refs.…”
Section: Related Workmentioning
confidence: 99%
“…The problem is called TSP with Neighborhoods (TSPN). A similar problem is the Close Enough TSP (CETSP) where the areas are defined by circles of different radius-see [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Yet, a recent review paper found that there have been extraordinarily few studies of the potential to transport dangerous goods by aircraft [50]. The literature mainly covered risk assessment [51], traffic flow prediction [52], vehicle routing [53], tour length optimization [54], facility locating, scheduling, aircraft loading [55], emergency response [56], and accident cause analysis [40].…”
Section: Transporting Dangerous Goodsmentioning
confidence: 99%